THE SUPERSELECTIVE EMBOLIZATION OF THE BRANCHES OF RENAL ARTERY — THE SALVATION OF ORGAN! - Y. G. Alyaev; N. A. Grigoriev; S. A. Kondrashin; N. I. Sorokin; G. A. Martirosyan (Сеченовский вестник, 2012)
Iatrogenic bleeding is the most common complication that arises after open and endoscopic benefits in kidneys. Predisposing factors of bleeding in the postoperative period may be in violation of the blood coagulation system and in the healing process of the vascular wall, as well as in infectious and inflammatory complications. When conservative therapy is ineffective, surgical treatment is necessary. In all of our observations was the cause of bleeding damage of segmental arteries and veins to the formation of arteriovenous fistulas. Application of superselective embolization of bleeding vessels allowed us to produce a reduction of abnormal blood flow with a maximum organ-effect.